Acquired Factor VIII Inhibitors: Three Cases - Kyaw, T.Z.; Jayaranee, S.; Bee, P.C.; Chin, E.F.M. (Galenos Yayinevi, 2013)
Acquired hemophilia A is a rare, but devastating bleeding disorder caused by spontaneous development of autoantibodies directed against coagulation factor VIII. In 40%-50% of patients it is associated with such conditions as the postpartum period, malignancy, use of medications, and autoimmune diseases; however, its cause is unknown in most cases. Acquired hemophilia A should be suspected in patients that present with a coagulation abnormality, and a negative personal and family history of bleeding. Herein we report 3 patients with acquired hemophilia A that had different underlying pathologies, clinical presentations, and therapeutic responses. Factor VIII inhibitor formation in case 1 occurred 6 months after giving birth; underlying disorders were not identified in cases 2 or 3. The bleeding phenotype in these patients’ ranged from no bleeding tendency with isolated prolongation of APTT (activated partial thromboplastin time) to severe intramuscular hematoma and hemarthrosis necessitating recombinant activated factor VII infusion and blood components transfusion. Variable responses to immunosuppressive treatment were also observed.